(untitled) (Heritage, 2020)
This paper is based on a field research of musical and folkloric materials of the Serbian population in the central part of Kosovo and Metohija, which was conducted in the period from 2015 to 2017 by the authors. During the specified time period, the authors recorded extensive collection of materials dominated by various forms of vocal expressions, and a special place is given to the wedding songs which are part of various ritual activities present in the current practice of the area. It is a part of the testimony of folk verbal and musical statements, and especially the participatory observation of the wedding ceremony that we attended in Gracanica, on September 6, 2015. Focusing on our participation in the wedding ritual in Gracanica, as a sort of paradigmatic form of this process in a wider (specified) territory, we point to the specific sustainability of traditional wedding practice, through consideration of actional, temporal, locative, personal and musical-poetic systems, in diachronic and the synchronous plane. Special attention is given to the musical component of the wedding ceremony, as well as the analysis of songs which usually function as a musical time frame of the wedding ritual. Perceiving musical characteristics of the songs through the analysis of melodies, tonal sequences, meters and other features will enable perception of the characteristics of the genre itself. Nevertheless, locating musical texts in a certain time and space enhances the importance of singing performances within the entire ritual complex.